IMPACT OF ORTHOTICS ON FLATFOOT MANAGEMENT: A COMPREHENSIVE REVIEW - Dr. Jagpreet Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
IMPACT OF ORTHOTICS ON FLATFOOT MANAGEMENT: A COMPREHENSIVE REVIEW Dr. Jagpreet Singh Flatfoot, medically termed as Pes Planus, is a common condition characterized by the collapse or loss of the longitudinal arch of the foot, resulting in the entire sole coming into near-complete contact with the ground. This condition can be classified into flexible and rigid types, with flexible flatfoot being more prevalent among individuals, especially during childhood. In flexible flatfoot, the arch reappears when the foot is unloaded, while in rigid flatfoot, the arch remains collapsed even when there is no weight-bearing. The underlying causes of flatfoot can range from genetic predispositions and ligamentous laxity to neuromuscular disorders, trauma, or obesity, each contributing to variations in its severity and presentation. This condition is observed not only in children, where it is often considered physiological and self-resolving, but also in adults, where it may lead to symptomatic pain and functional impairment if left untreated.